2021
DOI: 10.17582/journal.sja/2021/37.4.1134.1143
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Effect of Addition of Date Pit Powder and Soy Protein Isolate on Physicochemical Properties of Date Bars

Abstract: Current study was aimed to formulate a nutritious snack bar by incorporating date pit powder (by product) and soy protein isolate in date paste. Date bars were formulated after ingredients optimization and were analyzed for physico-chemical, in-vitro starch and protein digestibility, antioxidants and microbial count. Results showed that date bars are rich source of protein, fiber, carbohydrates and fat with good digestibility properties. Date pit powder and soy protein isolate incorporation enhanced the total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 21 publications
4
5
0
Order By: Relevance
“…The results were in accordance with the study performed by Ref. [ 39 ], who reported that DPP is a stable food product with low moisture content. Resultantly the treatments of date bars formulated with date pit powder depicted less moisture content and caused the reduction in water activity of samples supplemented with DPP.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…The results were in accordance with the study performed by Ref. [ 39 ], who reported that DPP is a stable food product with low moisture content. Resultantly the treatments of date bars formulated with date pit powder depicted less moisture content and caused the reduction in water activity of samples supplemented with DPP.…”
Section: Resultssupporting
confidence: 93%
“…The results were in accordance with the study performed by Ref. [ 39 ], who reported that samples of date bars with the supplementation of DPP and soy protein isolate showed significant enhancement in ash content. Another study revealed that during storage of three months, non-significant change (p > 0.05) was observed in the ash content of mixed araca and marola Jam [ 41 ].…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations